بناء برنامج تعليمي قائم على الوسائط المتعددة في تعلم مفردات اللغة العربية وتعليمها عبر برنامج "موودل" في ضوء احتياجات الطلبة في الجامعة الإسلامية العالمية بماليزيا – Bina’ barnamij ta’limi a’la al-wasa’it al-muta’addidah fi ta’allum mufradat al-lughah al-arabiyyah wa ta’limiha ‘abra barnamij Moodle fi dhaw’ ihtiyajat al-talabah fi al-jami’ah al-islamiyyah al-‘alamiyyah bi maliziya - Zainuddin, Nurkhamimi; Sahrir, Muhammad Sabri
This study attempts to analyze needs and principles for design and development of multimedia program for teaching and learning Arabic vocabulary via a platform namely Moodle. The researchers mentioned about the research tools, research samples and steps which are related to the design and development process. This study used “Needs Analysis Questionnaire” in conducting its research procedures. 100 level-one students and two lecturers from the Center for Foundation Studies, International Islamic University Malaysia had participated in the study which was carried out during the semester two of 2013/2014 academic year. The authors employ the results of these needs analysis in the development of multimedia program for teaching and learning Arabic vocabulary via Moodle and learned through the Moodle.